Acute efects of the Paulinia cupana, "Guaraná" on the cognition of normal volunteers - Galduróz, José Carlos Fernandes; Carlini, Elisaldo de Araújo (São Paulo Medical Journal, 1994)
The authors studied the acute effects of "Guaraná", when compared to caffeine and placebo, (double blind study) on cognition, anxiety and sleep in 30 normal volunteers. Although results were negative it cannot be concluded that "Guaraná" is harmless. Other studies shall be undertaken, administering "Guaraná" on a long term basis, as popularly proclaimed.